Optical Measurements of Presynaptic Release in Mutant Zebrafish Lacking Postsynaptic Receptors - Li, Weiyan (J Neurosci, 2003)
Differentiation of presynaptic nerve terminals is mediated, in part, through contact with the appropriate postsynaptic target cell. In particular, studies using dissociated nerve and muscle derived from Xenopus embryos have indicated that the properties of transmitter release from motor neurons are altered after contact with skeletal muscle. This maturation of presynaptic function has further been linked to retrograde signaling from muscle that involves activation of postsynaptic ACh receptors. Using FM1-43 optical determinants of exocytosis, we now compare calcium-mediated exocytosis at neuromuscular junctions of wild-type zebrafish to mutant fish lacking postsynaptic ACh receptors. In response to either high-potassium depolarization or direct electrical stimulation, we observed no differences in the rate or extent of FM1-43 destaining. These data indicate that the acquisition of stimulus-evoked exocytosis at early developmental stages occurs independent of both postsynaptic receptor and synaptic responses in zebrafish.